The Role of The Interdiscipline Approach in Islamic Study on The Religiusity of The Millenial Generation in The Digitalization Age - Muhammad Alinafiah; M. Bagus Ridwan; Salman Ahmadi (Budapest International Research and Critics University, 2022)
This study aims to examine the role of an interdisciplinary approach in Islamic studies on the religiosity of the millennial generation in the digital era. This study used descriptive qualitative method. When collecting data about phenomenological phenomena. The results of the study examine the role of an interdisciplinary approach in Islamic studies on the religiosity of the millennial generation in the digital era. The development of an increasingly advanced era has influenced diversityMillennial religiosity in the digital age. In the dimension of human thought, Islam shows that understanding Islam is not enough just through one particular approach or science, but requires many approaches based on different disciplines. Therefore, it is necessary to have an interdisciplinary approach. In Islam, this is done with the help of historical (historical) approaches, philosophy, sociology, religious anthropology and others. In the process of understanding Islam. Islam experienced a very high development.